2012
DOI: 10.3184/096034012x13317275660176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environment on the scale formed on oxide dispersion strengthened FeCrAl at 1050°C and 1100°C

Abstract: The surface scale formed on specimens of a commercial oxide dispersion strengthened (ODS) FeCrAl alloy (PM2000 2 ) exposed for 1 and 500 h at 1050 C in dry O 2 , Air þ 10%H 2 O and Ar þ 10%H 2 O consisted of a two-layer a-Al 2 O 3 structure with a columnar grain inner layer and a finer grain outer layer. The alumina scales formed in Air þ 10%H 2 O and Ar þ 10%H 2 O were slightly more than half of the thickness of the scale formed in dry O 2 . The same two-layer structure was also observed after exposure for 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 24 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Figures 1b and 1c show maps from a region at the metal-scale interface where Hf, but not Ti, was found to segregate to an adjacent grain boundary. It was recently discovered that Ti can be depleted in FeCrAl adjacent to the scale and not segregated to the adjacent grain boundaries [24]. This same behaviour was observed in X4 þ La with Ti found segregated to the alumina grain boundaries closer to the gas interface [23].…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…Figures 1b and 1c show maps from a region at the metal-scale interface where Hf, but not Ti, was found to segregate to an adjacent grain boundary. It was recently discovered that Ti can be depleted in FeCrAl adjacent to the scale and not segregated to the adjacent grain boundaries [24]. This same behaviour was observed in X4 þ La with Ti found segregated to the alumina grain boundaries closer to the gas interface [23].…”
Section: Methodsmentioning
confidence: 81%
“…The rapid outward transport of Ti may explain the lack of Ti segregation if Ti becomes depleted in the substrate. Some indication of this has been found on yttria-dispersed FeCrAl [24].…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Water vapor also could affect the transport through the alumina scale. Recent work studying the isothermal alumina scale growth rate in the presence of water vapor has shown that water vapor reduces the scale thickness at 1100°-1200°C [57,58]. However, these studies were conducted on FeCrAl-type alloys that do not form base-metal oxide layers like NiCrAl or NiPtAl compositions.…”
Section: Hvof/aps Coatings At 1100°cmentioning
confidence: 99%
“…Oxidation of Metals (2020) 93:229-245 beneficial, in particular, at lower temperatures as it accelerates protective alumina scale growth [16][17][18][19][20][21][22][23][24]. 3.…”
mentioning
confidence: 99%